(untitled) - Gosselin, Tom (Hoboken, N.J., 2007)
Practical Negotiating is an innovative, resourceful, and—as its name implies—practical guide to the art and science of negotiating. Unlike many books on negotiating, which are filled with theories and anecdotes, this one is rich with examples, tactics, and tips, which makes it the indispensable book when you are going into any negotiation
Keywords: Negotiation in business,Negotiation,Đàm phán trong kinh doanh,Nghệ thuật đàm phán